Acute hyperglycemia abolishes cardioprotection by remote ischemic perconditioning. Issue 1 (December 2015) - Baranyai, Tamás; Nagy, Csilla; Koncsos, Gábor; Onódi, Zsófia; Károlyi-Szabó, Melinda; Makkos, András; Varga, Zoltán; Ferdinandy, Péter; Giricz, Zoltán
Abstract Background Remote ischemic perconditioning (RIPerC) has a promising therapeutic insight to improve the prognosis of acute myocardial infarction. Chronic comorbidities such as diabetes are known to interfere with conditioning interventions by modulating cardioprotective signaling pathways, such as e.g., mTOR pathway and autophagy. However, the effect of acute hyperglycemia on RIPerC has not been studied so far. Therefore, here we investigated the effect of acute hyperglycemia on cardioprotection by RIPerC. Methods Wistar rats were divided into normoglycemic (NG) and acute hyperglycemic (AHG) groups. Acute hyperglycemia was induced by glucose infusion to maintain a serum glucose concentration of 15–20 mM throughout the experimental protocol. NG rats received mannitol infusion of an equal osmolarity. Both groups were subdivided into an ischemic (Isch) and a RIPerC group. Each group underwent reversible occlusion of the left anterior descending coronary artery (LAD) for 40 min in the presence or absence of acute hyperglycemia. After the 10-min LAD occlusion, RIPerC was induced by 3 cycles of 5-min unilateral femoral artery and vein occlusion and 5-min reperfusion. After 120 min of reperfusion, infarct size was measured by triphenyltetrazolium chloride staining. To study underlying signaling mechanisms, hearts were harvested for immunoblotting after 35 min in both the NG and AHG groups. Results Infarct size was significantly reduced by RIPerC in NG, but not in the AHG group (NG + Isch: 46.27 ± 5.31 % vs. NG + RIPerC: 24.65 ± 7.45 %, p < 0.05; AHG + Isch: 54.19 ± 4.07 % vs. 52.76 ± 3.80 %). Acute hyperglycemiaper se did not influence infarct size, but significantly increased the incidence and duration of arrhythmias. Acute hyperglycemia activated mechanistic target of rapamycine (mTOR) pathway, as it significantly increased the phosphorylation of mTOR and S6 proteins and the phosphorylation of AKT. In spite of a decreased LC3II/LC3I ratio, other markers of autophagy, such as ATG7, ULK1 phopsphorylation, Beclin 1 and SQSTM1/p62, were not modulated by acute hyperglycemia. Furthermore, acute hyperglycemia significantly elevated nitrative stress in the heart (0.87 ± 0.01 vs. 0.50 ± 0.04 µg 3-nitrotyrosine/mg protein, p < 0.05). Conclusions This is the first demonstration that acute hypreglycemia deteriorates cardioprotection by RIPerC. The mechanism of this phenomenon may involve an acute hyperglycemia-induced increase in nitrative stress and activation of the mTOR pathway.